The Importance of User-Generated Content in the news industry - Al-Jazeera News Channel Twitter to Spread Breaking News- أهميّة المحتوى الذي ينشئه المستخدم في صناعة الأخبار - إستخدام قناة الجزيرة لتويتر لنشر الأخبار العاجلة- - AbdEsselem GHERABI (Université de M'sila, 2022)
The study aims to reveal the importance of news- User Generated Content, by analyzing Al Jazeera’s Twitter dependence on information. The Study Used the "Content Analysis" Method to analyze 200 Tweets collected from Al Jazeera satellite television, from October 01 to 15, 2020, and the results indicated that they relied on user tweets to share breaking news, focusing mainly on political news rather than any other kind of tweets. We also have the most interaction, and we believe that this study will provide important insights into future research on Twitter, and we hope that it will contribute to new environmental media research, especially on the type and source of content used in news from traditional media organizations.
Keywords: User-Generated Content, news, Al-Jazeera News Channel, Twitter